Pendampingan Peningkatan Efisiensi Biaya Produksi UMKM Heriyanto Melalui Analisis Biaya Kualitas - Yulia Maulidyanti Rosdiana; Iriyadi Iriyadi; Diah Wahyuningsih (LPPM Institut Bisnis dan Informatika Kesatuan, 2020)
In each production process, it is possible there will be a discrepancy between the product that has been produced and with the standard, which referred to a defective product or a damaged product. The defective product or damaged product will affect the increase in production costs because the defective product has absorbed production costs from the beginning and it can cause losses to the company. Thus the company must make quality improvements to make the quality of the products produced more consistent and so that there are no more defective products. Improvement of this quality is needed by the existence of expenditure which is called quality cost. Quality costs are part of the production costs. With the existence of defective products or damaged products, it will cause production costs to increase because the company must pay for the process of reworking or reproducing. Therefore, by improving quality through quality costs, it is expected that production costs will be reduced. Production processes that pay attention to quality will reduce the possibility of product defects. Thus the company's production costs will be more efficient but still pay attention to the quality of the products produced. The purpose of this report is to find out how to supervise quality costs of UMKM in improving production cost efficiency. The author conducts community service at the UMKM Heriyanto which is a UMKM engaged in the shoe industry, especially adult women's shoes located on Jl. E. Sumawijaya, Sindang Barang Village, Gang Jambekiuna, Pasir Eurih Village, Taman Sari District, Bogor Regency.The results of the study show that the quality cost component found in the UMKM Heriyanto consists of prevention costs, internal failure costs, and external failure costs. In UMKM Heriyanto there is no apprasial cost because there is no quality control or checking activity for the product. In addition, the calculation of production costs in UMKM Heriyanto is quiet basic and simple because it does not separate the cost of direct raw materials from indirect raw materials, direct labor with indirect labor, and there are some overhead costs that are not taken into account. Internal failure costs consisting of excess raw materials have a significant influence on the cost of producing shoes for UMKM Heriyanto for all types of shoes. Thus the excess of this raw material must be reduced because it can affect the amount of raw material costs directly on production costs. If UMKM Heriyanto can implement the calculation of this quality cost, then in the next production it can reduce the cost of excess raw materials and UMKM Heriyanto can make production cost efficiency of 15%. Keywords: qualitycosts, production cost, cost effieciency